Are choices for higher education linked to the secondary school attended? - Dupont, Virginie; Lafontaine, Dominique (Swiss Journal of Educational Research, 2018)
In this article, we investigated students’ choices for higher education at the end of secondary education in the French Community of Belgium. Aspirations were analyzed according to personal features (gender, SES, tracks attended, having repeated a grade), and also to the composition of the school attended (effect of education offer academic mix and social mix). The results of multilevel analysis show that aspirations for higher education still depends on the features of the school where the student was enrolled in at the end of his/her secondary education even after controlling for personal features. Social composition of the school is directly linked with tertiary studies choices while academic mix is not.